2018
DOI: 10.1590/s0104-40362018002601507
|View full text |Cite
|
Sign up to set email alerts
|

ICT and home-educating families: a qualitative multiple case study

Abstract: While education is being increasingly permeated by Information and Communication Technologies (ICT), the current school is considered outdated and hardly capable of responding to the challenges of our time. Home Education emerges as a growing alternative, especially in developing countries, where it is not yet properly regulated and developed. This article presents a qualitative multiple case study focused on exploring the use of ICT by 70 Colombian families who educate at home. Data analysis was conducted fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
2
0
3
Order By: Relevance
“…It can be confirmed that digital devices are quickly becoming the tools of culture at home (NAEYC 2012, p. 2). Thus, family habits (customs and culture) make a difference in the involvement of children with ICT (MARSH et al, 2005;MCPAKE et al, 2005;PINEDA, CHIAPPE, 2018). As has been seen in the present study, children learn by observing other members of the family (older siblings, parents, grandparents or any other adult) (BROOKER, 2002;TOMANOVIĆ, 2004).…”
Section: Discussionmentioning
confidence: 52%
“…It can be confirmed that digital devices are quickly becoming the tools of culture at home (NAEYC 2012, p. 2). Thus, family habits (customs and culture) make a difference in the involvement of children with ICT (MARSH et al, 2005;MCPAKE et al, 2005;PINEDA, CHIAPPE, 2018). As has been seen in the present study, children learn by observing other members of the family (older siblings, parents, grandparents or any other adult) (BROOKER, 2002;TOMANOVIĆ, 2004).…”
Section: Discussionmentioning
confidence: 52%
“…Parents are essential in supporting the teaching–learning process of their children and this is why digital communication with teachers must be constant and fluid (Franky & Chiappe, 2018 ). In this context, Romero et al ( 2021 ) offers a series of proposals aimed at families regarding the education of their children in relation to media and informational education, how to supervise and teach responsible use of the internet or create spaces for communication between families and minors on digital media.…”
Section: Related Workmentioning
confidence: 99%
“…La educomunicación, mediante su praxis a través de la radio, puede generar espacios dialógicos significativos entre las culturas, pudiendo ser un punto fértil y apropiado para la resolución de conflictos. En vínculo con los medios de comunicación y las TIC y sus mediaciones, ofrece formas de hacer efectiva y expansiva la expresión y voz de todos quienes se involucran en las dinámicas entre culturas (Franky & Chiappe, 2018).…”
Section: Educomunicación Con Interculturalidad Y Viceversaunclassified